O Grupo Escolar Lauro Sodré em face da política de expansão do sistema escolar no estado do Pará: institucionalização, organização curricular e trabalho docente (1968-2008) - COSTA, Renato Pinheiro da (Universidade Federal do Pará, 2012)
In the present investigation aimed to understand the importance of educational institutions in the materialized elementary schools created in the era of Republican Brazil and its impact on the federal unit of Pará, analyzing the influence of his deployment to the organization of society and the formation of the citizen from the founding of the Group School Lauro Sodré between the historical period from 1968 to 2008. Adopted as a research method to document analysis, having as theoretical research based on documentary sources, iconographic and bibliographic, tracing the historic line of institutionalization of primary education developed in the elementary schools with its dissemination and implementation in the municipalities, interacting and modifying the social structures, economic and cultural cities, which led to the reconstruction work of the aspects surrounding the formation and work of teachers belonging to such a context, the curriculum structure and methodologies used in the process of institutional consolidation of primary education. Guided by questions problem: What is the importance of educational institutions in the organization of society and schooling of the Brazilian citizen?; How to materialize the integration of elementary schools in the education system of Para and what implications they brought the social structure of the second unit federated Governmental speeches?; How important geopolitical and educational primary school established in Lauro Sodré County Moju?; What were the requirements for the exercise of teaching and how they conducted the curriculum practices of these individuals at this institution? For the elementary schools are identified as the first republican project used to secure the Brazilian population between the ideals of their philosophy and ideology and in another phase of history as a means to prepare the manpower to leverage the country's progress, in this manner these education institutions have become spaces of achievements, conflicts and tensions in order to uncover the various situations that were involved in its context.